Determinants of Financial Management Behavior amongFishing Entrepreneurs: The Roles of Income, Social Support and Mental Accounting - Senda Yunita Leatemia; Emi Boki; Sari Tamayani Tjio; Paskanova Christi Gainau; Zalni Zalni; Revi Wilhelmina Silooy (Universitas Hayam Wuruk Perbanas, 2026)
This study examines the determinants of financial management behavior among fishing entrepreneurs by investigating the effects of income, social support, and mental accounting, while also assessing the moderating role of mental accounting. Data were collected through a convenience sampling survey of 152 fishing entrepreneurs on Ambon Island, Maluku Province, Indonesia. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings indicate that income does not have a significant effect on fishermen's financial management behavior, whereas social support and mental accounting have significant positive effects. In addition, the results show that mental accounting does not significantly moderate the relationships between income and financial management behavior or between social support and financial management behavior.